Analisis Pengaruh Harga , Kualitas Pelayanan, dan Lokasi Terhadap Keputusan Pembelian Hotel Syariah (Studi Pada Pelanggan Hotel Syariah Di Surakarta) - WIJIATMOKO, ANDRI (2016)
This research own the target to analyse the price have the influence to decision purchasing of hotel Moslem law in Surakarta. To analyse the service quality have the influence to decision purchasing of hotel Moslem law in Surakarta. To analyse the location have the influence to decision purchasing of hotel Moslem law in Surakarta. This Research use the population that is all cutomer exist in Hotel of Moslem law Surakarta, while sampel used in this research as much 70 accurate responder. Pursuant to result of price variable have the influence which signifikan to decision purchasing of hotel Moslem law in Surakarta. Variable of service Quality have the influence which signifikan to decision purchasing of Hotel Moslem law in Surakarta. Location Variable have the influence which signifikan to decision purchasing of Hotel Moslem law in Surakarta, while result analyse the Ftest by together price, service quality and location by together to decision of purchasing of Hotel Moslem law in Surakarta. So that model used is fit and result of test of coefficient determinasi (R2) obtained in scored a point doubled analysis regresi coefficient determinasi by adjusted-R2 equal to 0,655. Matter this means that 65,5% variation of explainable purchasing decision variable by price, service quality and location while the rest that is 34,5% explained by other factors outside accurate model